New distribution-free memory-type control charts based on the Wilcoxon rank-sum statistic. Issue 2 (4th March 2021) - Malela-Majika, Jean-Claude
ABSTRACT: In this paper, a new distribution-free double exponentially weighted moving average (DEWMA) control chart based on the Wilcoxon rank-sum (WRS) test without any distributional assumption of the underlying quality process is proposed. The proposed chart is the extension of the exponentially weighted moving average (EWMA) WRS control chart where the EWMA WRS statistic is applied twice. The ability of the EWMA and DEWMA WRS charts to detect small to large process mean shifts is further improved by combining each of them with the Shewhart control chart based on the WRS statistic. The in-control and out-of-control performances of the proposed charts are thoroughly investigated using extensive simulations. It is found that the proposed charts perform better than their competitors under both normal and non-normal distributions. A numerical illustration using real-life dataset is given in order to demonstrate the design and implementation of the new charts.